Supercapacitors: Improving the Performance of Paper Supercapacitors Using Redox Molecules from Plants (Adv. Sustainable Syst. 8/2019). (14th August 2019) - Edberg, Jesper; Brooke, Robert; Granberg, Hjalmar; Engquist, Isak; Berggren, Magnus
Abstract : In article number1900050, Jesper Edberg and co‐workers use the redox‐active dye molecule alizarin to enhance the energy storage capacity of all‐organic paper‐supercapacitors. The electrochemical performance and secondary doping effect of the dye on the conductive polymer PEDOT:PSS is investigated, and symmetric redox‐enhanced supercapacitor devices are demonstrated. This research shows how materials from plants can be used for green energy storage technologies.